Fact-Checking Politicians - Andrea Mattozzi; Samuel Nocito; Francesco Sobbrio (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the reaction of Italian Members of Parliament to a rigorous fact-checking of their public statements. Our research design relies on a novel randomized field experiment in collaboration with the leading Italian fact-checking company. Our results show that politicians are responsive to negative fact-checking. Specifically, we observe a significative reduction in the number of incorrect statements made by politicians after being treated. This effect persists for at least two months. We also observe a reduction in the probability of politicians making verifiable statements, suggesting that fact-checking may also increase the ambiguity of politicians' statements.
Keywords: D72; D78; D80; D91; 330; fact-checking; politicians; accountability; verifiability; ambiguity; RCR